Handoff latency analysis of mobile IPv6 protocol variations - Haseeb, Shariq; Ismail, Ahmad Faris (Elsevier, 2007)
Mobile Ipv6 (MIPv6) is a protocol proposed for the future all-IP mobile Internet access. The goal of MIPv6 is to provide uninterrupted network connectivity while moving between different domains or access points. To date, there are various technologies under development for enhancing and optimizing the existing MIPv6 protocol. Using three simulated scenarios, this paper compares the effects of these variations on the handoff latency. The first simulation scenario studies the latency of linear movement of mobile nodes; and the second scenario studies the latency of ping-pong (continuous changing of domains) movement of mobile nodes; the third scenario studies latency, handoff success and effect of signaling load on handoffs by gradually increasing from 5 nodes to 50 nodes. The experimental scenarios were simulated in an open source Network Simulator 2 (ns-2). This paper also discusses the deployment challenges and proposes the most suitable variation of the Mobile IPv6 protocol for reducing handoff latency.